GAMBARAN STATUS GIZI PADA PASIEN TUBERKULOSIS PARU (TB PARU) YANG MENJALANI RAWAT JALAN DI RSUD ARIFIN ACHMAD PEKANBARU - Elsa Puspita; Erwin Christianto; Indra Yovi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTPulmonary tuberculosis (Pulmonary TB) becomes a major public health problem in Indonesia. According to the World Health Organization (WHO) estimated that one-third of the world’s population is infected by mycrobacterium tuberculosis. In 1992, the WHO has declared tuberculosis as a global emergency. One of the factors that influence the spread of pulmonary tuberculosis is nutritional status. The aim of this research is to describe the nutritional status of outpatients with pulmonary tuberculosis at Arifin Achmad Pekanbaru General Hospital. This research uses descriptive method with cross sectional approach. The population in this research were all outpatients with pulmonary tuberculosis in pulmonary clinic of Arifin Achmad Pekanbaru General Hospital. The samples in this research were 71 people were taken with consecutive sampling method. The result showed that there were 67,6% male and 32,4% female, most patients were on productive age (18-55) there were 84,5%. Characteristic based on occupation and education showed 22,5% were employee and 49,3% have middle education. 83,1% were old patients and 76,1% of patients has been taking treatment > 2 months. There were 56.3% patients with good appetite. The most common nutritional status based on body mass index is normal category (46,5%) and nutritional status based on MUAC measurements, there were 49,3% patients with ideal nutritional category. The risk of malnutrition with malnutrition universal screening tools method showed most patient at high risk category (60.6%).Keywords : pulmonary tuberculosis, nutritional status, malnutrition universal screening tools